Implementation of The Trias Politica Concept and The Prospects For Establishing New High State Institutions in Indonesia - Tiopan, Demson; Setiawan, Agus; Rabbani, Kevin Alim (Universitas Ekasakti, 2023)
State institutions play a significantly central role in the implementation of governance. The doctrine of trias politica has been implemented in the structure of the Indonesian state, establishing a division of powers among three branches: the executive, legislative, and judicial. Nevertheless, over time, Indonesia has expanded the trias politica doctrine by incorporating a novel branch of power, namely the examinative institution operated by the The Audit Board of the Republic of Indonesia. The high state institutions established in accordance with the constitution enjoy robust and enduring positions and authorities. On the other hand, state institutions formed through legislation tend to possess comparatively weaker and non-permanent positions and authorities, as they are susceptible to amendments or even dissolution by the House of People’s Representatives (Dewan Perwakilan Rakyat, DPR), which holds legislative functions. The Ombudsman and Corruption Eradication Commission (Komisi Pemberantasan Korupsi or KPK), as auxiliary state institutions playing pivotal roles in the governance system, face vulnerability due to their establishment being founded on statutory laws. Consequently, there arises an urgent necessity and opportunity for the establishment of a new high state institution by elevating the Ombudsman and KPK to the status of high state institutions. However, there are inherent challenges that must be navigated, specifically the requirement for an amendment to the 1945 Indonesian Constitution, contingent upon the political will of the members of the People's Consultative Assembly (Majelis Permusyawaratan Rakyat or MPR).